Kegiatan Menggambar Bebas Menggunakan Crayon Dalam Upaya Meningkatkan Kreativitas Anak Usia Dini - Veryawan Veryawan; Juliati Juliati; Rapita Aprilia (UIN Sultan Maulana Hasanudin Banten, 2020)
This study aims to determine the mastery of the teacher's strategy in delivering free drawing learning materials using crayons that can increase children's creativity, provide interesting learning media in learning activities so that children's creativity can increase, provide opportunities for students to express all their ideas and ideas without any restrictions. in expressing colors in pictures and the teacher can understand and adjust learning outcomes with a standard level of achievement of children according to the stages of development. Classroom Action Research is a research process carried out by researchers through reflection with the aim of improving performance so that student learning outcomes increase. The planning model used is: Planning (planning), action (acting), observation (observing) and reflection (reflecting). The subjects in this improvement research were the children of group B TK Firza, totaling 15 children consisting of 6 boys and 9 girls. The field of development in this research is creativity with the activity is free drawing using crayons. The results showed the level of success in doing free drawing using crayons to improve children's creativity showed very good development and had reached the level of development in accordance with expectations, namely 80%. Thus, through free drawing activities using crayons can increase children's creativity.